Dual-channel gas diffusion layer and preparation method thereof
By depositing single-wall carbon nanotube functional layer on the carbon paper substrate and etching grooves, combining hydrophobic slurry to form a hydrophobic microporous layer, the performance contradiction of the gas diffusion layer under different humidity environments is solved, and the efficiency of fuel cells is achieved Wetting and mass transfer properties broaden the scope of application.
Patent Information
- Application Number
- CN202411874483.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-19
- Publication Date
- 2025-01-17
- Estimated Expiration
- 2044-12-19
Smart Images

Figure CN119324232A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of proton exchange membrane fuel cells, and in particular to a dual-channel gas diffusion layer and a preparation method thereof. Background Art
[0002] Proton exchange membrane fuel cell (PEMFC) is a hydrogen power generation device with outstanding advantages such as high efficiency, zero emission and continuous power generation. It is a promising new energy technology. In the actual operation of the battery, protons are transported in the proton exchange membrane as hydrated protons (H3O + ) is conducted from the anode to the cathode in the form of a liquid, which is a key factor in determining battery performance. Its proton conductivity is linearly related to the water content in the membrane, so the proton exchange membrane must be well hydrated to ensure its proton conductivity in a dry environment. However, excessive liquid water will cover the reactive sites of the cathode catalyst layer and block the gas transmission channels, causing "flooding", increasing the oxygen diffusion resistance, and thus reducing the mass transfer performance of the battery. Therefore, efficient water / gas management is crucial to achieving a high-performance PEMFC system.
[0003] The gas diffusion layer is generally composed of a substrate layer and a microporous layer. It is responsible for multiple functions such as supporting the catalyst layer, collecting current, transmitting gas and managing water. It is one of the key materials that affect the performance of the membrane electrode. The traditional microporous layer is usually a mixture of carbon black powder and a hydrophobic agent. It has strong hydrophobicity, which helps to remove water smoothly and provides advantages under high humidity conditions, but accelerates membrane dehydration and hinders proton conductivity under low humidity conditions. The gas diffusion layer modified with hydrophilic materials or hydrophilic coatings can effectively prevent "membrane drying" and improve the power generation performance of the battery in a dry environment. Lim et al. (Lim, IS; Kang, B.; Park, JY; Kim, MS Performance improvement of polymerelectrolyte membrane fuel cell by gas diffusion layer with atomic-layer-deposited HfO2 on microporous layer. Energy Convers. Manage. 2021, 236,114070. https: / / doi.org / 10.1016 / j.enconman.2021.114070.) prepared HfO2-GDL by atomic layer deposition. The addition of the hydrophilic layer significantly improved the water retention capacity of the gas diffusion layer and reduced the membrane resistance. However, traditional hydrophilic materials have poor conductivity, which greatly increases the internal resistance of the fuel cell, and the adsorbed liquid water can easily block the gaps, hinder the diffusion of the reaction gas, and reduce the mass transfer performance. In past reports, hydrophilic microporous layers were mostly prepared by mixing hydrophilic multi-walled carbon nanotubes with different carbon powders or by in-situ growing carbon nanotubes. Studies have found that the dispersion of multi-walled carbon nanotubes in the microporous layer slurry is poor and the hydrophilic areas are randomly distributed, making it difficult to achieve effective water vapor transport.
[0004] At present, the work on improving water / gas management in gas diffusion layers still cannot effectively solve the contradiction between "membrane drying" and "water flooding" (i.e. water retention and mass transfer). The improvement of self-humidification performance under dry conditions is often at the expense of mass transfer performance under high humidity conditions, and the water vapor transmission is disordered. Summary of the invention
[0005] The object of the present invention is to provide a dual-channel gas diffusion layer and a preparation method thereof in view of the deficiencies in the prior art.
[0006] To achieve the above object, the technical solution adopted by the present invention is:
[0007] The first aspect of the present invention is to provide a method for preparing a dual-channel gas diffusion layer, the steps comprising:
[0008] S1, depositing a single-walled carbon nanotube dispersion on a hydrophobic carbon paper substrate, and sequentially performing washing, drying, calcining and etching to obtain a single-walled carbon nanotube functional layer;
[0009] S2, coating the hydrophobic slurry on the surface of the single-walled carbon nanotube functional layer and performing sintering treatment to obtain the dual-channel gas diffusion layer.
[0010] Preferably, in step S1, the method for preparing the single-walled carbon nanotube dispersion comprises: performing an oxidation treatment on the single-walled carbon nanotubes by an acid oxidation method, and then performing an ultrasonic treatment to obtain the single-walled carbon nanotube dispersion.
[0011] More preferably, the outer diameter of the single-walled carbon nanotube is 1-4 nm, the length is 5-30 μm, the oxygen-carbon ratio of the single-walled carbon nanotube after oxidation treatment is 0.1-0.3; the concentration of the single-walled carbon nanotube dispersion is 0.001-0.1 mg.mL -1 .
[0012] Preferably, in step S1, the deposition includes at least one of suction filtration, dip coating, spray coating or spin coating.
[0013] Preferably, in step S1, the washing treatment comprises: washing with deionized water for 1-10 times; the drying treatment temperature is 60-80°C; the calcination treatment temperature is 300-380°C, and the calcination treatment time is 10-60min.
[0014] Preferably, in step S1, the etching process is laser etching, the power of the laser etching is 5-30 W, the speed is 50-5000 mm / s, and the frequency is 10-80 kHz.
[0015] Preferably, in step S2, the method for preparing the hydrophobic slurry comprises: mixing carbon powder, a hydrophobic agent, a solvent and Triton X-100 by ball milling in a mass ratio of 1: (0.1-1.0): (1-15): (0.1-0.5) to obtain the hydrophobic slurry.
[0016] More preferably, the carbon powder is at least one of Ketjen black, whisker carbon nanotubes or acetylene black; the hydrophobic agent is at least one of polytetrafluoroethylene, polyvinylidene fluoride or fluorinated ethylene propylene copolymer; and the solvent is at least one of deionized water, ethanol or isopropanol.
[0017] Preferably, in step S2, the coating method of the hydrophobic slurry is one of spraying, wire rod coating or scraper coating.
[0018] Preferably, in step S2, the sintering treatment comprises: raising the room temperature to 230-280°C at a rate of 2-15°C / min, keeping the temperature for 20-60min, raising the temperature to 350-380°C at a rate of 2-15°C / min, keeping the temperature for 20-60min, and finally cooling down.
[0019] The second aspect of the present invention is to provide a dual-channel gas diffusion layer prepared by the above-mentioned preparation method, comprising: a carbon paper substrate layer, a single-walled carbon nanotube functional layer and a hydrophobic microporous layer stacked in sequence;
[0020] The single-walled carbon nanotube functional layer is provided with a plurality of grooves, and the bottom end of the hydrophobic microporous layer is embedded in the grooves.
[0021] Preferably, the shape of the groove includes at least one of a rectangle, a square, a circle or a triangle.
[0022] Preferably, the depth of the groove is 0.01-1 μm, and the area of the groove is 0.01-400 mm 2 The interval between adjacent grooves is 0.1-20 mm.
[0023] Preferably, the water contact angle of the carbon paper substrate layer is in the range of 120°-150°.
[0024] Preferably, the thickness of the single-walled carbon nanotube functional layer is 0.01-1.0 μm.
[0025] Preferably, the water contact angle of the single-walled carbon nanotube functional layer is in the range of 60°-120°.
[0026] Preferably, the hydrophobic microporous layer has a thickness of 20-100 μm.
[0027] The present invention adopts the above technical solution, and has the following technical effects compared with the prior art:
[0028] The present invention arranges a single-walled carbon nanotube functional layer on the carbon paper substrate layer and arranges grooves on the single-walled carbon nanotube functional layer, which not only ensures that the carbon paper substrate layer has sufficient supporting force, but also enables the single-walled carbon nanotube functional layer to form a structure with hydrophilic and hydrophobic periodic distribution;
[0029] The single-walled carbon nanotube functional layer of the present invention has reasonable wettability and microporous structure, which is conducive to the storage of liquid water. A plurality of regularly distributed grooves on the surface of the single-walled carbon nanotube functional layer are filled with a hydrophobic slurry and serve as gas flow channels to achieve orderly transmission of water / gas. Water generated by the cathode reaction is preferentially concentrated and stored in the hydrophilic area, and the remaining hydrophobic areas provide a channel for oxygen to quickly reach the catalytic layer. The present invention improves the performance of the gas diffusion layer by adjusting the balance between hydrophilicity and hydrophobicity, ensures the wetting of the proton membrane in the fuel cell, and improves the mass transfer performance at the same time. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 Schematic diagram of the basic structure of a dual-channel gas diffusion layer in Example 1 of the present invention;
[0031] Figure 2 The performance test results under 20% RH in the test embodiment of the present invention are shown; wherein, the solid mark is the polarization curve; and the half-hollow mark is the power density curve;
[0032] Figure 3 The performance test results under 100% RH conditions in the test examples of the present invention are shown in FIG. 1 , wherein the solid mark is the polarization curve, and the half-hollow mark is the power density curve. DETAILED DESCRIPTION
[0033] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0034] It should be noted that, in the absence of conflict, the embodiments of the present invention and the features in the embodiments may be combined with each other.
[0035] The present invention will be further described below with reference to the accompanying drawings and specific embodiments, but they are not intended to limit the present invention.
[0036] Example 1
[0037] This embodiment provides a method for preparing a dual-channel gas diffusion layer, the steps comprising:
[0038] S1. Single-walled carbon nanotubes with an outer diameter of 1 nm and a length of 5 μm were oxidized by acid oxidation. The oxygen-carbon ratio of the oxidized single-walled carbon nanotubes was 0.1. The concentration of 0.001 mg.mL was prepared under the assistance of high-power ultrasound. -1 A dispersion of single-walled carbon nanotubes;
[0039] The single-walled carbon nanotube dispersion was deposited on a hydrophobic carbon paper substrate by spraying to form a single-walled carbon nanotube layer with a thickness of 0.01 μm, which was washed once with deionized water, dried at 60°C, and calcined at 300°C for 10 min to obtain a single-walled carbon nanotube functional layer. The laser etching power was set to 5 W, the speed was set to 5000 mm / s, and the frequency was set to 10 kHz. Multiple 0.01 mm2 single-walled carbon nanotube functional layers were etched on the surface of the single-walled carbon nanotube functional layer. 2 , rectangular grooves with a spacing of 0.1 mm;
[0040] S2. Ketjen black (KBs), fluorinated ethylene propylene copolymer (FEP), deionized water and Triton X-100 are ball-milled in a mass ratio of 1:0.1:1:0.1 to obtain a hydrophobic slurry, and the slurry is coated on the surface of the single-walled carbon nanotube functional layer with grooves by spraying. The sintering is then carried out by heating the temperature from room temperature to 230°C at a rate of 2°C / min, keeping the temperature for 20 minutes, and then heating the temperature to 350°C at a rate of 2°C / min, keeping the temperature for 20 minutes, and then cooling the temperature to obtain a dual-channel gas diffusion layer.
[0041] like Figure 1 As shown, the dual-channel gas diffusion layer includes: a carbon paper substrate layer, a single-walled carbon nanotube functional layer and a hydrophobic microporous layer stacked in sequence;
[0042] The single-walled carbon nanotube functional layer is provided with a plurality of grooves, and the bottom end of the hydrophobic microporous layer is embedded in the grooves.
[0043] Example 2
[0044] This embodiment provides another method for preparing a dual-channel gas diffusion layer, the steps comprising:
[0045] S1. Single-walled carbon nanotubes with an outer diameter of 2 nm and a length of 10 μm were oxidized by acid oxidation. The oxygen-carbon ratio of the oxidized single-walled carbon nanotubes was 0.15. The concentration of 0.005 mg.mL was prepared under the assistance of high-power ultrasound. -1 A dispersion of single-walled carbon nanotubes;
[0046] The single-walled carbon nanotube dispersion was deposited on a hydrophobic carbon paper substrate by dip coating to form a single-walled carbon nanotube layer with a thickness of 0.1 μm, which was washed with deionized water for 3 times, dried at 60°C, and calcined at 330°C for 20 min to obtain a single-walled carbon nanotube functional layer. The laser etching power was set to 10 W, the speed was set to 3000 mm / s, and the frequency was set to 20 kHz. Multiple 1.44 mm2 single-walled carbon nanotube functional layers were etched on the surface of the single-walled carbon nanotube functional layer. 2 , square grooves with a spacing of 5 mm;
[0047] S2. Carbon powder (whisker carbon nanotubes WCNTs: acetylene black ACET is 6:4), polyvinylidene fluoride (PVDF), deionized water and Triton X-100 are ball-milled in a mass ratio of 1:0.3:2:0.2 to obtain a hydrophobic slurry, which is then coated on the surface of the single-walled carbon nanotube functional layer with grooves by a wire rod coating method. The sintering is then performed from room temperature to 250°C at a rate of 5°C / min, and the temperature is kept for 30 minutes. The temperature is then continued to be increased to 360°C at a rate of 5°C / min, and the temperature is kept for 30 minutes. The temperature is then cooled to obtain a dual-channel gas diffusion layer.
[0048] Example 3
[0049] This embodiment provides another method for preparing a dual-channel gas diffusion layer, the steps comprising:
[0050] S1. Single-walled carbon nanotubes with an outer diameter of 3 nm and a length of 15 μm were oxidized by acid oxidation. The oxygen-carbon ratio of the oxidized single-walled carbon nanotubes was 0.3. The concentration of 0.01 mg.mL was prepared under the assistance of high-power ultrasound. -1 A dispersion of single-walled carbon nanotubes;
[0051] The single-walled carbon nanotube dispersion was deposited on a hydrophobic carbon paper substrate by suction filtration to form a single-walled carbon nanotube layer with a thickness of 0.6 μm, which was washed with deionized water for 5 times, dried at 60°C, and calcined at 350°C for 30 min to obtain a single-walled carbon nanotube functional layer. The laser etching power was set to 20 W, the speed was set to 1000 mm / s, and the frequency was set to 60 kHz. Multiple etchings with an area of 113.04 mm were made on the surface of the single-walled carbon nanotube functional layer. 2 , circular grooves with a spacing of 10 mm;
[0052] S2. Carbon powder (whisker carbon nanotubes WCNTs: KBs is 8:2), polytetrafluoroethylene (PTFE), solvent (isopropanol: deionized water is 2:1) and Triton X-100 are ball-milled in a mass ratio of 1:0.6:5:0.3 to obtain a hydrophobic slurry, which is then coated on the surface of the single-walled carbon nanotube functional layer with grooves by a doctor blade coating method. The sintering is then carried out from room temperature to 260°C at a rate of 10°C / min, and the temperature is kept for 30 minutes. The temperature is then continued to be raised to 360°C at a rate of 10°C / min, and the temperature is kept for 30 minutes. The temperature is then cooled to obtain a dual-channel gas diffusion layer.
[0053] Example 4
[0054] This embodiment provides another method for preparing a dual-channel gas diffusion layer, the steps comprising:
[0055] S1. Single-walled carbon nanotubes with an outer diameter of 4 nm and a length of 30 μm were oxidized by acid oxidation. The oxygen-carbon ratio of the oxidized single-walled carbon nanotubes was 0.3. The concentration of 0.1 mg.mL was prepared under the assistance of high-power ultrasound. -1 A dispersion of single-walled carbon nanotubes;
[0056] The single-walled carbon nanotube dispersion was deposited on a hydrophobic carbon paper substrate by suction filtration to form a single-walled carbon nanotube layer with a thickness of 1 μm, which was washed with deionized water for 10 times, dried at 80°C, and calcined at 380°C for 60 min to obtain a single-walled carbon nanotube functional layer; the laser etching power was set to 25 W, the speed was 500 mm / s, and the frequency was 70 kHz, and multiple 205 mm2 single-walled carbon nanotube functional layers were etched on the surface of the single-walled carbon nanotube functional layer. 2 , triangular grooves with a spacing of 15 mm;
[0057] S2. Carbon powder (WCNTs:ACET is 5:3), PTFE, deionized water and Triton X-100 are ball-milled in a mass ratio of 1:0.8:10:0.5 to obtain a hydrophobic slurry, which is then coated on the surface of the grooved single-walled carbon nanotube functional layer by a doctor blade coating method. The sintering is then carried out from room temperature to 280°C at a rate of 15°C / min, and the temperature is kept for 60 minutes. The temperature is then raised to 380°C at a rate of 15°C / min, and the temperature is kept for 60 minutes. The temperature is then cooled to obtain a dual-channel gas diffusion layer.
[0058] Comparative Example 1
[0059] This comparative example provides a method for preparing a gas diffusion layer, the steps comprising:
[0060] Firstly, carbon powder (WCNTs:KBs is 8:2), PTFE, solvent (isopropanol:deionized water is 2:1) and TritonX-100 are ball-milled in a mass ratio of 1:0.6:10:0.3 to obtain a hydrophobic slurry, which is then coated on the surface of a hydrophobically treated carbon paper substrate by a doctor blade coating method, and then sintered from room temperature to 260°C at a rate of 10°C / min, kept warm for 30 minutes, continued to be heated to 360°C at a rate of 10°C / min, kept warm for 30 minutes, and then cooled to obtain the gas diffusion layer.
[0061] Comparative Example 2
[0062] This comparative example provides another method for preparing a gas diffusion layer, the steps comprising:
[0063] Step 1: single-walled carbon nanotubes with an outer diameter of 3 nm and a length of 15 μm are oxidized by acid oxidation, with an oxygen-carbon ratio of 0.3; a concentration of 0.01 mg.mL is prepared under the assistance of high-power ultrasound.-1 A dispersion of single-walled carbon nanotubes;
[0064] Step 2, depositing the carbon nanotube dispersion on a hydrophobic treated carbon paper substrate by suction filtration to form a single-walled carbon nanotube film layer with a thickness of 0.6 μm, washing with deionized water for 5 times, drying at 60° C., and calcining at 350° C. for 30 min;
[0065] Step 3, ball-milling and mixing carbon powder (WCNTs:KBs is 8:2), PTFE, solvent (isopropanol:deionized water is 2:1) and TritonX-100 in a mass ratio of 1:0.6:10:0.3 to obtain a hydrophobic slurry, and coating it on the surface of the single-walled carbon nanotube film layer in step 2 by a doctor blade coating method, and then sintering, heating from room temperature to 260°C at a rate of 10°C / min, keeping warm for 30 minutes, and continuing to heat to 360°C at a rate of 10°C / min, keeping warm for 30 minutes, and then cooling to obtain the gas diffusion layer.
[0066] Comparative Example 3
[0067] This comparative example provides another method for preparing a gas diffusion layer, the steps comprising:
[0068] S1. Single-walled carbon nanotubes with an outer diameter of 2 nm and a length of 30 μm were oxidized by acid oxidation. The oxygen-carbon ratio of the oxidized single-walled carbon nanotubes was 0.2. The concentration of 0.1 mg.mL was prepared under the assistance of high-power ultrasound. -1 A dispersion of single-walled carbon nanotubes;
[0069] The single-walled carbon nanotube dispersion was deposited on a hydrophobic carbon paper substrate by suction filtration to form a single-walled carbon nanotube layer with a thickness of 0.8 μm, which was washed with deionized water for 3 times, dried at 80°C, and calcined at 360°C for 30 min to obtain a single-walled carbon nanotube functional layer. The laser etching power was set to 35 W, the speed was 30 mm / s, and the frequency was 85 kHz. Multiple layers with an area of 400 mm were etched on the single-walled carbon nanotube functional layer and the carbon paper substrate. 2 , square grooves with a spacing of 20 mm;
[0070] S2. Carbon powder (WCNTs: multi-walled carbon nanotubes MWCNTs: ACET is 5:3:2), PTFE, isopropanol and TritonX-100 are ball-milled in a mass ratio of 1:1:15:0.5 to obtain a hydrophobic slurry, which is then coated on the surface of the single-walled carbon nanotube functional layer with grooves by a doctor blade coating method. The sintering is then carried out from room temperature to 280°C at a rate of 15°C / min, and the temperature is kept for 60 minutes. The temperature is then raised to 380°C at a rate of 15°C / min, and the temperature is kept for 60 minutes. The temperature is then lowered to obtain a gas diffusion layer.
[0071] Comparative Example 4
[0072] This comparative example provides another method for preparing a dual-channel gas diffusion layer, the steps comprising:
[0073] S1. Single-walled carbon nanotubes with an outer diameter of 5 nm and a length of 1 μm were oxidized by acid oxidation. The oxygen-carbon ratio of the oxidized single-walled carbon nanotubes was 0.3. The concentration of 0.1 mg.mL was prepared under the assistance of high-power ultrasound. -1 A dispersion of single-walled carbon nanotubes;
[0074] The single-walled carbon nanotube dispersion was deposited on a hydrophobic carbon paper substrate by suction filtration to form a single-walled carbon nanotube layer with a thickness of 1 μm, which was washed with deionized water for 10 times, dried at 80°C, and calcined at 380°C for 60 min to obtain a single-walled carbon nanotube functional layer; the laser etching power was set to 25 W, the speed was 500 mm / s, and the frequency was 70 kHz, and multiple 205 mm2 single-walled carbon nanotube functional layers were etched on the surface of the single-walled carbon nanotube functional layer. 2 , triangular grooves with a spacing of 15 mm;
[0075] S2. Carbon powder (WCNTs:ACET is 5:3), PTFE, deionized water and Triton X-100 are ball-milled in a mass ratio of 1:0.8:10:0.5 to obtain a hydrophobic slurry, which is then coated on the surface of the grooved single-walled carbon nanotube functional layer by a doctor blade coating method. The sintering is then carried out from room temperature to 280°C at a rate of 15°C / min, and the temperature is kept for 60 minutes. The temperature is then raised to 380°C at a rate of 15°C / min, and the temperature is kept for 60 minutes. The temperature is then cooled to obtain a dual-channel gas diffusion layer.
[0076] Comparative Example 5
[0077] This comparative example provides another method for preparing a dual-channel gas diffusion layer, the steps comprising:
[0078] S1. Single-walled carbon nanotubes with an outer diameter of 4 nm and a length of 30 μm were oxidized by acid oxidation. The oxygen-carbon ratio of the oxidized single-walled carbon nanotubes was 0.01. The concentration of 0.1 mg.mL was prepared under the assistance of high-power ultrasound. -1 A dispersion of single-walled carbon nanotubes;
[0079] The single-walled carbon nanotube dispersion was deposited on a hydrophobic carbon paper substrate by suction filtration to form a single-walled carbon nanotube layer with a thickness of 1 μm, which was washed with deionized water for 10 times, dried at 80°C, and calcined at 380°C for 60 min to obtain a single-walled carbon nanotube functional layer; the laser etching power was set to 25 W, the speed was 500 mm / s, and the frequency was 70 kHz, and multiple 205 mm2 single-walled carbon nanotube functional layers were etched on the surface of the single-walled carbon nanotube functional layer. 2 , triangular grooves with a spacing of 15 mm;
[0080] S2. Carbon powder (WCNTs:ACET is 5:3), PTFE, deionized water and Triton X-100 are ball-milled in a mass ratio of 1:0.8:10:0.5 to obtain a hydrophobic slurry, which is then coated on the surface of the grooved single-walled carbon nanotube functional layer by a doctor blade coating method. The sintering is then carried out from room temperature to 280°C at a rate of 15°C / min, and the temperature is kept for 60 minutes. The temperature is then raised to 380°C at a rate of 15°C / min, and the temperature is kept for 60 minutes. The temperature is then cooled to obtain a dual-channel gas diffusion layer.
[0081] Detection Example
[0082] The dual-channel gas diffusion layers prepared in Examples 1-4 and the gas diffusion layers prepared in Comparative Examples 1-5 were cut into a size of 2 cm×2 cm, respectively, and assembled into single cells for performance testing.
[0083] The specific test conditions are:
[0084] The battery temperature was 80°C, the relative humidity (RH) of the cathode and anode was 100%, 60%, and 20%, and the stoichiometric ratio of oxygen / hydrogen was 14.4 / 7.2 (the current density was 1A / cm -2 ), cathode / anode back pressure 60kPa.
[0085] The test results are shown in Table 1 and Figure 2-3 As shown;
[0086] Table 1
[0087] From Table 1 and Figure 2-3 It can be seen that under the conditions of 20% RH and output voltage 0.6V (under this voltage, the battery needs to have a certain water storage capacity), the current density of Comparative Example 1 is significantly lower than that of Comparative Examples 2-3 and Examples 1-4, while under the conditions of 100% RH and output voltage 0.6V, its current density is significantly increased. It can be seen that Comparative Example 1 cannot achieve the water storage effect due to the lack of a single-walled carbon nanotube functional layer, and the battery performance is completely affected by the environment. The performance is poor when the ambient humidity is low, and its performance can be improved only when the ambient humidity is high.
[0088] Comparative Example 2 has a single-walled carbon nanotube functional layer, but no grooves are formed thereon. Although it can store water, it cannot balance hydrophobicity and water storage. Under the condition of an output voltage of 0.6V, the battery performance of Comparative Example 2 is not much different from that of Examples 1-4 because at this voltage, the battery needs to store water, and Comparative Example 2 has a single-walled carbon nanotube functional layer, which has a certain water storage capacity. However, under the condition of an output voltage of 0.2V, the battery needs to drain water. At this time, the current density of Comparative Example 2 is significantly lower than that of Examples 1-4, which shows that Comparative Example 2 does not have excellent drainage performance.
[0089] Under the condition of output voltage 0.2V in Comparative Example 3, the battery performance is significantly lower than that of Examples 1-4. This is because the laser etching energy is too high, which penetrates the single-walled carbon nanotube functional layer and breaks through the carbon paper substrate layer. The high-performance gas diffusion layer requires the substrate layer to have high rigidity to stably support the catalyst layer and the electrolyte membrane. Therefore, the formation of large holes on the carbon paper substrate layer makes the gas diffusion layer have poor mechanical properties, and it is easy to accumulate a large amount of water and difficult to discharge, thereby resulting in performance degradation.
[0090] Compared with Example 4, the performance of Comparative Example 4 is significantly worse within all test conditions. This is because the single-walled carbon nanotubes used therein are relatively small in length and diameter. On the one hand, the constructed porous functional layer is relatively loose and the conductivity is reduced. On the other hand, the single-walled carbon nanotube functional layer will partially fall off after laser treatment, thereby affecting the final performance of the membrane electrode in Comparative Example 4. For Comparative Example 5, under low humidity conditions, the performance of Comparative Example 5 is significantly lower than that of Example 4. This is because the single-walled carbon nanotubes therein have a very low surface oxygen content after oxidation treatment, and the oxygen-carbon ratio is only 0.01, which is much smaller than the oxygen-carbon ratio of Example 4. This reduces the wettability of the assembled single-walled carbon nanotube functional layer, resulting in poor water retention, thereby reducing battery performance.
[0091] The current density of Examples 1-4 under the environmental conditions increased to different extents, which means that the battery performance was greatly improved, indicating that the presence of the hydrophilic and hydrophobic dual channels in the structure can both retain water and improve mass transfer.
[0092] In summary, the dual-channel gas diffusion layer obtained by the present invention can optimize the performance of the battery under different humidity environments and broaden the application scope of the fuel cell.
[0093] The above description is only a preferred embodiment of the present invention, and does not limit the implementation mode and protection scope of the present invention. For those skilled in the art, it should be aware that all solutions obtained by equivalent substitutions and obvious changes made using the description and illustrations of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a dual-channel gas diffusion layer, characterized in that the steps include: S1, depositing a single-walled carbon nanotube dispersion on a hydrophobic carbon paper substrate, and sequentially performing washing, drying, calcining and etching to obtain a single-walled carbon nanotube functional layer; The preparation method of the single-walled carbon nanotube dispersion comprises: performing oxidation treatment on the single-walled carbon nanotubes by an acid oxidation method, and then performing ultrasonic treatment to obtain the single-walled carbon nanotube dispersion; the outer diameter of the single-walled carbon nanotubes is 1-4 nm, the length is 5-30 μm, and the oxygen-carbon ratio of the single-walled carbon nanotubes after oxidation treatment is 0.1-0.3; the concentration of the single-walled carbon nanotube dispersion is 0.001-0.1 mg.mL -1 ; The etching process is laser etching, the power of the laser etching is 5-30W, the speed is 50-5000mm / s, and the frequency is 10-80kHz; S2, coating the hydrophobic slurry on the surface of the single-walled carbon nanotube functional layer and performing sintering treatment to obtain the dual-channel gas diffusion layer.
2. The preparation method according to claim 1, characterized in that In step S2, the method for preparing the hydrophobic slurry comprises: mixing carbon powder, a hydrophobic agent, a solvent and Triton X-100 by ball milling at a mass ratio of 1: (0.1-1.0): (1-15): (0.1-0.5) to obtain the hydrophobic slurry.
3. The preparation method according to claim 2, characterized in that: The carbon powder is at least one of Ketjen black, whisker carbon nanotubes or acetylene black; the hydrophobic agent is at least one of polytetrafluoroethylene, polyvinylidene fluoride or fluorinated ethylene propylene copolymer; and the solvent is at least one of deionized water, ethanol or isopropanol.
4. The preparation method according to claim 1, characterized in that: In step S2, the sintering treatment includes: the room temperature is raised to 230-280°C at a rate of 2-15°C / min, kept at that temperature for 20-60min, then raised to 350-380°C at a rate of 2-15°C / min, kept at that temperature for 20-60min, and finally cooled.
5. A dual-channel gas diffusion layer prepared by the preparation method according to any one of claims 1 to 4, characterized in that: include: A carbon paper substrate layer, a single-walled carbon nanotube functional layer and a hydrophobic microporous layer are sequentially stacked; The single-walled carbon nanotube functional layer is provided with a plurality of grooves, and the bottom end of the hydrophobic microporous layer is embedded in the grooves.
6. The dual-channel gas diffusion layer according to claim 5, characterized in that: The shape of the groove includes at least one of a rectangle, a square, a circle or a triangle.
7. The dual-channel gas diffusion layer according to claim 5, characterized in that: The depth of the groove is 0.01-1 μm, and the area of the groove is 0.01-400 mm 2 The interval between adjacent grooves is 0.1-20 mm.
Citation Information
Patent Citations
Gas diffusion layer as well as preparation method and application thereof
CN112310413A
Fuel cell gas diffusion layer conductive slurry, gas diffusion layer and preparation method of gas diffusion layer
CN115359948A
Gas diffusion layer, preparation method thereof and fuel cell prepared from gas diffusion layer
CN118572127A
Gas diffusion layer with good water management performance and preparation method thereof
CN119108565A
Gas diffusion electrode base material and production method therefor, and solid polymer fuel cell
US20220029170A1